2001
DOI: 10.2460/ajvr.2001.62.1840
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD3 and CD11b antigens on blood and mammary gland leukocytes and bacterial survival in milk of cows with experimentally induced Staphylococcus aureus mastitis

Abstract: Activation of bovine mammary gland macrophages and T cells in response to intramammary infusion of S. aureus was associated with an inability to culture this bacterium from milk. Identification of specific inflammatory phases of S. aureus-induced mastitis in cows may allow for the design of more efficacious treatment and control programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
3
11
1
Order By: Relevance
“…A , B : Leukocyte profiles and microbial test results of 6 dairy cows inoculated at day 0 with non-methicillin resistant (non-MRSA) Staphylococcus aureus , followed over two weeks, are reported (total: 24 longitudinal observations, data previously reported, using a different analytical method [44]). C , D : Leukocyte profiles of 439 humans non-infected or infected by malaria, tested once, are reported, of whom five displayed high MC/N values and malaria-positive test results and were tested twice (two weeks apart), becoming malaria-negative in the later test (total: 444 observations, data previously reported, using a different analytical method [61]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A , B : Leukocyte profiles and microbial test results of 6 dairy cows inoculated at day 0 with non-methicillin resistant (non-MRSA) Staphylococcus aureus , followed over two weeks, are reported (total: 24 longitudinal observations, data previously reported, using a different analytical method [44]). C , D : Leukocyte profiles of 439 humans non-infected or infected by malaria, tested once, are reported, of whom five displayed high MC/N values and malaria-positive test results and were tested twice (two weeks apart), becoming malaria-negative in the later test (total: 444 observations, data previously reported, using a different analytical method [61]).…”
Section: Resultsmentioning
confidence: 99%
“…That can be achieved when one ratio estimates early host-microbial responses and the other ratio expresses late responses. For example, a 2D plot that includes N/L and MC/N ratios indicates early responses when the N/L ratio is high (e.g., much greater than 1), or late responses when the MC/N ratio is >1 [44][46]. Such structure can distinguish the temporal sequence of biological responses regardless of chronological scales (minutes/hours/days) and is robust to the absence (or presence) of slow (or fast) immune responders [47].…”
Section: Introductionmentioning
confidence: 99%
“…The extent of CD8 cells in milk was not consistent and varied dependent on the time after infection, and the cells in milk were increased at 9-14 days post-inoculation [27]. However, variations of immunophenotypes and their activities are commonly observed even in experimental studies with the same challenge of pathogens used [21,28,29]. In the present study, increases in respective CD4 and CD8 cells were found in milk from cows with naturally occurring chronic S. aureus mastitis, suggesting that inflammatory responses continue for a relatively long period in the mammary gland and cause the characteristic changes of lymphocyte profiles reflecting chronic infection by the S. aureus pathogen in dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…CD11b/CD18 dimer is one of β 2 -integrins expressed on PMN and it is called complement receptor 3 or Mac-1 (Rivas et al 2001). The expression of CD62L and CD11b on PMN are inversely regulated by chemotactic factors (Kishimoto et al 1989).…”
Section: Introductionmentioning
confidence: 99%